Does a Pro-Inflammatory Process Precede Alzheimer's Disease and Mild Cognitive Impairment? - T. Ferretti, M.; C. Cuello, A. (Current Alzheimer Research, 2011)
The occurrence of a plaque-dependent inflammation in Alzheimer's disease has been extensively documented in both human specimens and transgenic models of the disease. Since insoluble plaques are present in AD patients from early preclinical stages of the pathology, the point at which neuroinflammation first occurs in the progression of the AD pathology is still unknown. In this review we discuss the clinical and experimental evidence for the occurrence of inflammation in preclinical, asymptomatic phases of the progression of the AD pathology. In particular, we discuss the evidence from different transgenic models suggesting that a pro-inflammatory process might even be initiated prior to plaque deposition. The factors responsible for the early, pre-plaque inflammation are reviewed, with particular emphasis on the role of soluble Aβ-oligomers. Furthermore, we analyze the consequences of the microglial activation and the deregulation of NGF metabolism, in the context of the earliest amyloid pathology. Finally, we propose MMP-9 as a promising biomarker for signalling early stages of an ongoing CNS inflammation.
Keywords: inflammation